Does managed care make a difference? Physicians' length of stay decisions under managed and non-managed care - Groenewegen Peter P; Noetscher Cheryl M; Westert Gert P; de Jong Judith D (BMC, 2004)
Abstract Background In this study we examined the influence of type of insurance and the influence of managed care in particular, on the length of stay decisions physicians make and on variation in medical practice. Methods We studied lengths of stay for comparable patients who are insured under managed or non-managed care plans. Seven Diagnosis Related Groups were chosen, two medical (COPD and CHF), one surgical (hip replacement) and four obstetrical (hysterectomy with and without complications and Cesarean section with and without complications). The 1999, 2000 and 2001 - data from hospitals in New York State were used and analyzed with multilevel analysis. Results Average length of stay does not differ between managed and non-managed care patients. Less variation was found for managed care patients. In both groups, the variation was smaller for DRGs that are easy to standardize than for other DRGs. Conclusion Type of insurance does not affect length of stay. An explanation might be that hospitals have a general policy concerning length of stay, independent of the type of insurance of the patient.